2019
DOI: 10.1084/jem.20182313
|View full text |Cite
|
Sign up to set email alerts
|

Caveolin-1 selectively regulates microRNA sorting into microvesicles after noxious stimuli

Abstract: Emerging evidence suggests that extracellular vesicle (EV)–containing miRNAs mediate intercellular communications in response to noxious stimuli. It remains unclear how a cell selectively sorts the cellular miRNAs into EVs. We report that caveolin-1 (cav-1) is essential for sorting of selected miRNAs into microvesicles (MVs), a main type of EVs generated by outward budding of the plasma membrane. We found that cav-1 tyrosine 14 (Y14)–phosphorylation leads to interactions between cav-1 and hnRNPA2B1, an RNA-bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
183
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(193 citation statements)
references
References 73 publications
8
183
2
Order By: Relevance
“…The current accumulated knowledge about the mechanisms of ncRNAs sorting into secretory vesicles is focused on miRNAs in human and mammalian cells. Experimental evidence showed that the miRNA sorting into exosomes and other vesicles is mediated by RNA-binding and cytoskeleton proteins, following patterns that appear to be cell specific [40][41][42]. Interestingly, in human cells, the external perturbation of the expression of individual miRNAs or their cognate targets promotes bidirectional miRNA relocation from the cytoplasm to multivesicular bodies, controlling the miRNA sorting to exosomes [43].…”
Section: Conveyors For Ncrna Transport Between Cellsmentioning
confidence: 99%
“…The current accumulated knowledge about the mechanisms of ncRNAs sorting into secretory vesicles is focused on miRNAs in human and mammalian cells. Experimental evidence showed that the miRNA sorting into exosomes and other vesicles is mediated by RNA-binding and cytoskeleton proteins, following patterns that appear to be cell specific [40][41][42]. Interestingly, in human cells, the external perturbation of the expression of individual miRNAs or their cognate targets promotes bidirectional miRNA relocation from the cytoplasm to multivesicular bodies, controlling the miRNA sorting to exosomes [43].…”
Section: Conveyors For Ncrna Transport Between Cellsmentioning
confidence: 99%
“…Similarly, another RNA-binding protein, HNRNPA2B1, was reported to direct particular miRNA species to exosomes based on affinity for particular sequence motifs (Villarroya-Beltri et al, 2013). In addition, a recent study has found that a complex with caveolin-1 directs HNRNPA2B1 incorporation into microvesicles, and a post-translational modification induced by oxidative cell stress alters its selection for miRNA (Lee et al, 2019).…”
Section: Proteomic Content and Cargo Sortingmentioning
confidence: 99%
“…These models suggest that EVs indiscriminately incorporate miRNA; however, the majority of studies to date have actually found that EVs exhibit enrichment for particular RNA species, adding further complexity to the means of miRNA delivery (Li et al, 2013;Shurtleff et al, 2016;Wei et al, 2017). Different theories have been proposed to explain this phenomenon, such as a bias for particular sequence motifs or post-transcriptional RNA modifications that direct trafficking (Bolukbasi et al, 2012;Lee et al, 2019;Santangelo et al, 2016;Villarroya-Beltri et al, 2013). In addition, it appears that some miRNA species are principally trafficked to EVs by proteins other than those involved in classical miRNA maturation.…”
Section: Proteomic Content and Cargo Sortingmentioning
confidence: 99%
“…Alveolar macrophages and epithelial cells are two airway cell-types with readily apparent functional responses to O3 (1). Alveolar macrophages show reduced phagocytosis (17) and lung inflammation (33,43) are associated with altered airway EV miRNA profiles. In addition, there is growing evidence that EV miRNAs directly elicit airway cellular gene expression and phenotypic effects.…”
Section: Introductionmentioning
confidence: 99%